2021
DOI: 10.3389/fonc.2021.802592
|View full text |Cite
|
Sign up to set email alerts
|

Can Acute Postoperative Pain Management After Tumour Resection Surgery Modulate Risk of Later Recurrence or Metastasis?

Abstract: BackgroundCancer is a leading cause of mortality worldwide, but death is rarely from the primary tumour: Rather it is multi-organ dysfunction from metastatic disease that is responsible for up to 90% of cancer-related deaths. Surgical resection of the primary tumour is indicated in 70% of cases. The perioperative stress response, tissue hypoxia at the site of surgery, and acute pain contribute to immunosuppression and neo-angiogenesis, potentially promoting tumour survival, proliferation, and metastasis. Poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 124 publications
(128 reference statements)
0
8
0
Order By: Relevance
“…Propofol was reported to have less immunosuppression and has a lower inflammatory response than volatile drugs during the perioperative period (Lee et al, 2022). This may reduce opioid use for pain relief and may have favorable to contribute outcomes (Moorthy et al, 2021). Therefore, the net effects of propofol and inhalational agent sevoflurane on the oncologic outcomes in our patients remain unknown and this was the case for many studies, even clinical trials (Ishikawa et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Propofol was reported to have less immunosuppression and has a lower inflammatory response than volatile drugs during the perioperative period (Lee et al, 2022). This may reduce opioid use for pain relief and may have favorable to contribute outcomes (Moorthy et al, 2021). Therefore, the net effects of propofol and inhalational agent sevoflurane on the oncologic outcomes in our patients remain unknown and this was the case for many studies, even clinical trials (Ishikawa et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…61,62 Moreover, the inflammatory response caused by surgical resection will aggravate this effect. 54,55 Therefore, we further investigated the infiltration of immune cells and immunosuppressive cells in the postoperative tumors of the treated mice. In Figure 6A, in the recurrent tumor tissues of the PBS and CM groups, MDSCs (Gr-1 + CD11b + cells) and Treg cells (Fox3 + CD4 + CD25 + cells) accounted for a large proportion, whereas the CD8 + T cells and CD4 + T cells were scarce, demonstrating an intense immunosuppressive state in the recurrent tumors.…”
Section: Cp@cm Nanoparticles Downregulated Pd-l1 Expression and Reduc...mentioning
confidence: 99%
“…At least a part of the suppressive effect of LAs could occur via VGSC inhibition [ 16 ]. Disappointingly, however, regional anesthesia with lidocaine during tumor resection did not appear to have a significant effect on breast cancer outcomes including recurrence [ 17 ]. Nevertheless, it remained plausible that other anesthetic techniques (e.g., total intravenous anesthesia and systemic LA infusion) might influence the oncologic outcome in the resection surgery of other major tumors (e.g., colorectal and lung) [ 17 ].…”
Section: Therapeutic Modalitiesmentioning
confidence: 99%
“…Disappointingly, however, regional anesthesia with lidocaine during tumor resection did not appear to have a significant effect on breast cancer outcomes including recurrence [ 17 ]. Nevertheless, it remained plausible that other anesthetic techniques (e.g., total intravenous anesthesia and systemic LA infusion) might influence the oncologic outcome in the resection surgery of other major tumors (e.g., colorectal and lung) [ 17 ]. Indeed, a recent meta-analysis of cohort studies concluded that the use of a combined epidural–general anesthesia during surgery on patients with colon cancer could improve overall survival [ 18 ].…”
Section: Therapeutic Modalitiesmentioning
confidence: 99%